Pretreated exosomes by electrical stimulation accelerate bone regeneration - Jialu Chen; Jian Chen; Jiahao Chen; Renjie Lu; Ziyuan Liu; Yang Zhang; Chi Zhang (Bioactive Materials)
Bone tissue engineering has attracted significant attention from both the research and clinical communities. Inspired by the inherent bioelectric properties of bone tissue, electrical stimulation is widely recognized as an external intervention that can induce osteogenesis, mineralization, and accelerate bone regeneration. However, the clinical application of electrical stimulation is limited by the complexity of the procedures and the use of cumbersome, invasive equipment. Exosomes, as an alternative to seed cells, can overcome many of the limitations associated with stem cell transplantation. Researchers aim to enhance exosomes' therapeutic potential for bone regeneration. While various pretreatments have been studied, there is currently no research investigating the role of exosomes pretreated with electrical stimulation in bone tissue regeneration. In this study, we pretreated bone marrow mesenchymal stem cells (BMSCs) with electrical stimulation and isolated the resulting exosomes (Elec-exo). A series of in vitro experiments determined that 150 μA is the optimal condition for electrical stimulation. Mechanistically, proteomic analysis revealed an enrichment of proteins involved in “Oxidative Phosphorylation” regulation within Elec-exo, and transcriptomic analysis indicated the activation of Pl3k-Akt and MAPK bone formation-related signaling pathways in the effector cells. Hydrogels, as a sustained-release scaffold, were used to deliver Elec-exo in vivo. In a rat femur defect model, Elec-exo loaded into chondroitin sulfate methacrylate (CSMA) hydrogel accelerated early bone tissue regeneration. In summary, our study explores the mechanisms by which electrical stimulation pretreatment enhances bone tissue regeneration and broadens the therapeutic application of exosomes in accelerating bone regeneration.